2017
DOI: 10.1093/cercor/bhx131
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status and Reading Disability: Neuroanatomy and Plasticity in Response to Intervention

Abstract: SES AND NEUROANATOMY IN READING DISABILITY 2Although reading disability (RD) and socioeconomic status (SES) are independently associated with variation in reading ability and brain structure/function, the joint influence of SES and RD on neuroanatomy and/or response to intervention is unknown. Sixty-five children with RD (ages 6 to 9) with diverse SES were assigned to an intensive, 6-week summer reading intervention (n = 40) or to a waiting-list control group (n = 25). Before and after, all children completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
93
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(109 citation statements)
references
References 94 publications
9
93
2
1
Order By: Relevance
“…Consistent with previous studies that demonstrated modulatory influences of SES on the brain–reading relationship (Brito, Piccolo, & Noble, ; Gullick et al, ; Noble et al, ; Romeo et al, ), ILF FA in kindergarten was associated with better second‐grade reading outcomes in lower‐SES but not higher‐SES children. The longitudinal nature of the current findings is a notable difference from other studies that only examined the SES × brain association with reading concurrently.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with previous studies that demonstrated modulatory influences of SES on the brain–reading relationship (Brito, Piccolo, & Noble, ; Gullick et al, ; Noble et al, ; Romeo et al, ), ILF FA in kindergarten was associated with better second‐grade reading outcomes in lower‐SES but not higher‐SES children. The longitudinal nature of the current findings is a notable difference from other studies that only examined the SES × brain association with reading concurrently.…”
Section: Discussionsupporting
confidence: 89%
“…SES in childhood has profound and widespread implications for brain development (Hackman, Farah, & Meaney, ), with language and reading‐related brain structures being particularly affected (Noble & McCandliss, ; Noble, Tottenham, & Casey, ; Romeo et al, ; Rowe & Goldin‐Meadow, ). SES is thought to affect brain development, and subsequent behavioral outcomes, through a range of mediating factors such as maternal stress and cognitive stimulation (Hackman et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Family SES has been associated repeatedly with differences in children's brain structure, particularly in regions responsible for language and EF. Socioeconomic disadvantage has been associated with reduced cortical gray matter, as measured in terms of volume (Hair, Hanson, Wolfe, & Pollak, ; Jednoróg et al., ), thickness (Lawson, Duda, Avants, Wu, & Farah, ; Mackey et al., ; Romeo et al., ), and surface area (Noble et al., ). For example, in a study of 3‐ to 20‐year‐olds, higher family income and parental education were associated significantly with greater cortical surface area, independent of age, sex, and genetic ancestry (Noble et al., ).…”
Section: Socioeconomic Inequality and Brain Structure In Youthmentioning
confidence: 99%
“…The strongest effects were seen in the left perisylvian cortical regions underlying language processing, as well as in the regions of the prefrontal cortex (PFC) underlying EF. These neuroanatomical differences partially explained socioeconomic disparities in vocabulary (Romeo et al., ), EF (Noble et al., ), and standardized tests of academic achievement (Hair et al., ; Mackey et al., ).…”
Section: Socioeconomic Inequality and Brain Structure In Youthmentioning
confidence: 99%
See 1 more Smart Citation